PENERAPAN KEPENTINGAN YANG WAJAR (FAIR USE) MENGENAI MATERI HAK CIPTA DI INTERNET - sulasno, sulasno; Dwisvimiar, Inge (Hukum dan Masyarakat Madani, 2021)
The same and not justified laws such as acts of plagiarism or images without permission. Fair use doctrine or fair use (fair deadling, fair use). The most common sense of fair use is any use of copyrighted material or materials for a limited and transformative purpose.                       Reasonable interest is one of the protections that copyright law allows to use copyright in a reasonable and limited use in copyright work so as to minimize copyright infringement. But on the internet, there are many things that can happen. For example, copying existing in copyrighted Internet content may be considered a copyright infringement, opening music data and then uploading it without the permission of the Copyright Holder may also be categorized Copyright Infringement, reading articles to electronic books are also vulnerable to copyright infringement and others.                                         The most common sense of fair use is any use of copyrighted material or materials for a limited and transformative purpose. The term fair use is a doctrine in copyright law in the United States that allows the limited use of copyrighted works, without the permission of the rights holder. Another term is fair use. The use is limited to the importance of commenting, criticism, news reporting, research, and teaching